Antimony(iii) and bismuth(iii) amides containing pendant N-donor groups – a combined experimental and theoretical study. Issue 1 (11th November 2014) - Vránová, Iva; Jambor, Roman; Růžička, Aleš; Hoffmann, Alexander; Herres-Pawlis, Sonja; Dostál, Libor
Abstract : The synthesis and structural study dealing with antimony(iii ) and bismuth(iii ) amides, derivatives of a pyrrole core, with pendant nitrogen functionalities is presented. Abstract : N, N - and N, N, N -chelated antimony(iii ) and bismuth(iii ) chlorides L 1–3 MCl2 1–4 [for L 1 : M = Sb (1 ), for L 2 : M = Sb (2 ) and for L 3 : M = Sb (3 ) and Bi (4 )], containing ligands L 1–3 derived from the pyrrole ring (where L 1 = C4 H3 N-2-(CHN-2′, 6′- i Pr2 C6 H3 ), L 2 = C4 H2 N-2, 5-(CH2 NMe2 )2, L 3 = C4 H2 N-2, 5-(CH2 NC4 H8 )2 ), were prepared by the treatment of lithium precursors with SbCl3 or BiCl3 . Molecular structures of1–4 were described both in solution (NMR spectroscopy) and in the solid state (single-crystal X-ray diffraction analysis). Structures of1–4 were also subjected to a density functional theory study.